ChemInform Abstract: Computational Chemistry for NH3 Synthesis, Hydrotreating, and NOx Reduction: Three Topics of Special Interest to Haldor Topsoe. Issue 34 (August 2015) - Elnabawy, Ahmed O.; Rangarajan, Srinivas; Mavrikakis, Manos
Abstract Review: 141 refs.